Vicarious Punishment and War Crimes Prosecution: The Civil War or Alice Through the Looking Glass - Richard Arens (Washington University Law Quarterly, 1951)
Faced with an international crisis of the first magnitude, the United States is once again confronted with the problem of the invocation of sanctions for violations of the rectitude norm of American or world proportions. The problem may require intensive scrutiny as an outgrowth of the urgent demands of policy developments on a rapidly changing national and international scene. Inevitably an operative theory of sanctions is a function of the culture in which it is used at a given stage of its development. A quest for the dominant theory therefore should not confine itself to an examination of official doctrine but should probe further for the leitmotiv. It is submitted that the leitmotiv of American sanction theory, to the extent to which it has been manifested in the present crisis, is not encompassed in a more traditional pattern of modern philosophies of punishment embracing deterrence, the "categorical imperative, individual rehabilitation, or even the more drastic model of “measures of social defence” for “socially dangerous acts” propounded by Enrico Ferri. This leitmotiv, instead, is deemed to be embodied in what is a unique American contribution to the field of sanction theory. It has been variously described as the use of sanctions to maximize a transformation of the social scene, i.e. as an instrument of social change, or alternately, as a therapeutic agent for the “non-criminal” masses, intended, for example, for the purpose of reducing the existing tension levels, or as a “socially controlled catharsis.” Existing designations of this phase leave several vital elements out of account. It is these elements which constitute a point of inquiry in this study.
Keywords: War and emergency powers